МИНЕРАЛОГИЯ ЗОЛОТОНОСНОЙ РОССЫПИ САРБАЛАХ, ЮЖНАЯ ЯКУТИЯ - Гамянин Г.Н.; Жданов Ю.Я.; Сурнин А.А.; Попова С.К. (My University, 2005)
Mincralogical analysis was carried out for the non-electromagnetic fraction of heavy gold-bearing concentrate. Among heavy minerals occurring in intcrgrowth with gold, there were recorded magnetite, pyritc, galenite. Telluridcs and bismuth minerals: hcssite, coloradoite, tsumoite, native bismuth, are widespread there also. There were revealed numerous intermctallic compounds of the Au-Pb-Sb-Sn system, corresponding in composition as to known minerals - Au2Pb, Au(Pb,Sb)2, Au(Pb,Sn), so to other phases - АизРЬ and Au2Sn3 unknown in reference books. It is shown that carbonate composition of host rocks and interstratal intrusive magmatism become the favorable conditions for a formation of gold-rarc-metal placer-forming ores with intermctallic gold compounds in thermostatic reduction media.
Keywords: 549.411(571.S6)